2007
DOI: 10.1590/s0004-282x2007000600008
|View full text |Cite
|
Sign up to set email alerts
|

The history of spinocerebellar ataxia type 10 in Brazil: travels of a gene

Abstract: -The authors report the history of spinocerebellar ataxia 10 (SCA10), since its first report in a large Portuguese-ancestry Family with autosomal dominant pure cerebellar ataxia, till the final identification of further families without Mexican ancestry. These families present a quite different phenotype from those SCA10 families described in Mexico.KEY WORDS: spinocerebellar ataxia, spinocerebellar ataxia type 10, "pure" cerebellar ataxia.A história da ataxia espinocerebelar tipo 10 no Brasil: as viagens de u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…All SCA10 families in the Americas were of local indigenous ancestry. 1,[7][8][9] Brazilian patients with SCA10 ataxia present with a distinct phenotype of late onset pure cerebellar ataxia without epilepsy, differing from the Mexican phenotype in that aspect. Commonly, there is a slow progressive gait ataxia, with associated dysarthria and abnormal ocular dysmetria.…”
Section: Patientmentioning
confidence: 93%
See 2 more Smart Citations
“…All SCA10 families in the Americas were of local indigenous ancestry. 1,[7][8][9] Brazilian patients with SCA10 ataxia present with a distinct phenotype of late onset pure cerebellar ataxia without epilepsy, differing from the Mexican phenotype in that aspect. Commonly, there is a slow progressive gait ataxia, with associated dysarthria and abnormal ocular dysmetria.…”
Section: Patientmentioning
confidence: 93%
“…Commonly, there is a slow progressive gait ataxia, with associated dysarthria and abnormal ocular dysmetria. 1,8,9 Symptoms of neurodegenerative disorders are commonly exacerbated during pregnancy and postpartum. 10,11 The mechanism by which this heterogeneous group of disorders is precipitated by pregnancy is speculative.…”
Section: Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies (brain magnetic resonance imaging and computed tomography) showed cerebellar atrophy without overt brainstem or cerebral atrophy. Eighteen patients from the five families who were genotyped showed expanded SCA10 alleles containing 1,350–2,400 ATTCT repeats [3, 10]. The SCA10 repeat size inversely correlates with the age of onset in these Brazilian patients.…”
Section: Sca10—the Brazilian Casesmentioning
confidence: 99%
“…In both countries all SCA10 families reported Amerindian ancestry. 4,6,7,9 Two additional reports on nonBrazilian South American populations diagnosed with SCA 10 were published more recently. Gatto et al 10 reported on two SCA 10 Argentinean patients presenting with cerebellar ataxia and epilepsy, associated with additional motor signs (dystonia in one case and parkinsonism on the other).…”
mentioning
confidence: 99%